Supplementing the state conventional security agencies in crime prevention and control: A Visible option for community volunteers' guard in Benue State, Nigeria. (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The increasing crime waves such as banditry, kidnapping, killings, robbery and community invasion by herders have negatively impacted Benue communities, necessitating the enactment of a Community Volunteer Guard by the State Government in 2022 to complement conventional security agents. This study presents a practical analysis of Community Volunteer Guards' activities, strategies and challenges in tackling the rising crime wave by leveraging materials from primary and secondary sources. A qualitative approach was employed to obtaininformation from 20 participants. Their responses were thematically analysed, and the study found that volunteer guards used checkpoints and routine patrol in crime control in the study area. The study also found that arresting armed robbers, recovering stolen property, and protecting the community against theft were effective areas the volunteer guard achieved in crime control. However, inadequate equipment, poor training, and indiscipline were challenges for the volunteer guard. This study concludes that the intervention of community volunteer guards in Benue State crime control has positively impacted lives and properties. Hence, the study recommends that a standard means of recruiting community volunteer guards be observed. Additionally, the state government should provide more modern and sophisticated equipment to members of vigilante groups in Benue State.
Keywords: Banditry; Community Volunteer Guards; Crime Control; Effectiveness; Kidnapping